IEEE INFOCOM 2003. Twenty-Second Annual Joint Conference of the IEEE Computer and Communications Societies (IEEE Cat. No.03CH37
DOI: 10.1109/infcom.2003.1208685
|View full text |Cite
|
Sign up to set email alerts
|

Sampling biases in IP topology measurements

Abstract: Considerable attention has been focused on the properties of graphs derived from Internet measurements. Router-level topologies collected via traceroute studies have led some authors to conclude that the router graph of the Internet is a scale-free graph, or more generally a power-law random graph. In such a graph, the degree distribution of nodes follows a distribution with a power-law tail.In this paper we argue that the evidence to date for this conclusion is at best insufficient. We show that graphs appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
243
0
3

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(254 citation statements)
references
References 21 publications
4
243
0
3
Order By: Relevance
“…Biases of graphs induced by acquisition through a small number of traceroute monitors have been studied for instance in by Lakhina et al [12]. However, recent studies by Dall'Asta et al [25] and Guillaume et al [14] show that one may be quite confident of the accuracy, using this kind of exploration, of distances and degrees, which are the main properties that we study here.…”
Section: The Data Setmentioning
confidence: 78%
“…Biases of graphs induced by acquisition through a small number of traceroute monitors have been studied for instance in by Lakhina et al [12]. However, recent studies by Dall'Asta et al [25] and Guillaume et al [14] show that one may be quite confident of the accuracy, using this kind of exploration, of distances and degrees, which are the main properties that we study here.…”
Section: The Data Setmentioning
confidence: 78%
“…Figure 2 shows that vps with higher degree tend to have more agents (using degrees extracted from RouteViews produced the same results). This indicates that this is not a sampling bias caused by measurement artifact [16] but rather a hint that large ASes tend to "host" more agents. Additionally, vps with a single agent in them are mostly in the midlevel degrees section, and vps with more than one agent are scattered in a wide variety of degrees.…”
Section: B Data Filteringmentioning
confidence: 89%
“…Lakhina et al [16] showed that AS degrees inferred using traceroute-like sampling technique, are highly affected by the location of the vps. The authors claimed that this bias could cause the observed power-law distribution, and suggested as a criteria for detecting bias in traceroute studies to check whether the highest-degree ASes tend to be near the measuring sources.…”
Section: E Sampling Biasmentioning
confidence: 99%
“…Traditionally, much graph discovery research has been conducted in the context of today's complex networks such as the Internet which have fascinated scientists for many years, and there exists a wealth of results on the topic. One of the most influential measurement studies on the Internet topology was conducted by the Faloutsos brothers [12], and their work has subsequently been intensively discussed both in practical [17] and theoretical [2] papers. The classic instrument to discover Internet topologies is traceroute [7], but the tool has several problems which renders the problem challenging.…”
Section: Related Workmentioning
confidence: 99%